CrS2 Supported Transition Metal Single Atoms as Efficient Bifunctional Electrocatalysts: A Density Functional Theory Study - Wang, Ying (ChemEngineering, 2025)
Transition metal dichalcogenides (TMDs) are recognized for their exceptional energy storage capabilities and electrochemical potential, stemming from their unique electronic structures and physicochemical properties. In this study, we focus on chromium disulfide (CrS2) as the primary research subject and employ a combination of density functional theory (DFT) and first-principle calculations to investigate the effects of incorporating transition metal elements onto the surface of CrS2. This approach aims to develop a class of bifunctional single-atom catalysts with high efficiency and to analyze their catalytic performance in detail. Theoretical calculations reveal that the Au@CrS2 single-atom catalyst demonstrates outstanding catalytic activity, with a low overpotential of 0.34 V for the oxygen evolution reaction (OER) and 0.37 V for the oxygen reduction reaction (ORR). These results establish Au@CrS2 as a highly effective bifunctional catalyst. Moreover, the catalytic performance of Au@CrS2 surpasses that of traditional commercial catalysts, such as Pt (0.45 V) and IrO2 (0.56 V), suggesting its potential to replace these materials in fuel cells and other energy applications. This study provides a novel approach to the design and development of advanced transition metal-based catalytic materials.